A four-factor model of consumption values in a multicultural society: Measurement invariance and the duality of materialism and frugality in Qatar - Hamad Al-Ibrahim; Arokiasamy Perianayagam; Noor Al Thani (PLoS ONE, 2026)
Societies undergoing rapid economic modernization face a tension between materialist consumption and sustainability, yet few psychometrically sound tools exist to measure these values in non-Western contexts. This study aimed to develop and validate a scale of consumption values in the multicultural, high-income setting of Qatar. We conducted a large-scale survey (N = 2,026) of Qatari nationals and expatriates using a comprehensive questionnaire. Exploratory factor analysis revealed four distinct and interpretable dimensions of consumption values: (1) Materialism/Social Status, an orientation valuing luxury and wealth as markers of success; (2) Extravagance, a tendency toward impulsive and unnecessary spending; (3) Frugality, a disposition toward thrift and careful budgeting; and (4) Environmental Consciousness, a concern for the ecological impact of consumption. A four-factor model was confirmed using confirmatory factor analysis, demonstrating good model fit. Multi-group analyses established measurement invariance (configural, metric, and scalar) across nationality, gender, and income groups, ensuring that comparisons between these groups are meaningful. Latent mean comparisons revealed that Qatari nationals scored significantly higher on Materialism and Extravagance but lower on Frugality than expatriates. Critically, materialism and extravagance were associated with poorer self-reported financial well-being, whereas frugality was linked to better financial standing. This research provides a robust, multi-dimensional instrument for assessing consumption values in diverse societies and offers insights into the psychological factors shaping financial and environmental outcomes in modernizing economies.